Media at lipunan - Tolentino, Rolando B.; Santos, Josefina M.C. (Diliman, Quezon City : The University of the Philippines Press, 2014)
The series anchored on producing a distinct Philippine, as writings in the textbooks are interdisciplinal and authored by Filipino scholars.
Seksyon 1. Introduksyon -- Seksyon 2. Media at Ekonomiya -- Seksyon 3. Media, Politika at Pamumuno -- Seksyon 4. Media at Kultura -- Seksyon 5. Media at Ideolohiya -- Seksyon 6. Mediya at kulturang pagbabago -- Appendix. Media and society course syllabus.
Includes bibliographical references and index.
Keywords: MASS MEDIA -- PHILIPPINES -- SOCIAL ASPECTS; MASS MEDIA -- PHILIPPINES -- STUDY AND TEACHING (HIGHER); MASS MEDIA IN COMMUNITY DEVELOPMENT